2010
DOI: 10.4088/jcp.09m05089gry
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Attention-Deficit/Hyperactivity Disorder (ADHD) Treatment on Smoking Cessation Intervention in ADHD Smokers

Abstract: Objective High smoking rates in adults with attention deficit hyperactivity disorder (ADHD) and nicotine’s amelioration of ADHD suggest that effective ADHD treatment might facilitate abstinence in smokers with ADHD. The present study evaluated if using osmotic release methylphenidate (OROS-MPH) to treat ADHD enhances response to smoking cessation treatment in smokers with ADHD. Method A randomized, double-blind, placebo-controlled, 11-week trial with a one month follow-up conducted at six clinical sites betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 42 publications
11
103
2
Order By: Relevance
“…Prolonged abstinence was used as the primary outcome (Y) in these analyses, with complete abstinence and Week 10 PPA serving as confirmatory outcome measures. All analyses pooled data across the two treatment groups from the original study (OROS-MPH and placebo), as we previously established that there was no effect of OROS-MPH on smoking cessation outcomes in the study sample (Winhusen et al, 2010). Table 2 shows the results of bootstrapped regressions examining the three predictor variables-desire to quit, perceived difficulty quitting, and expected success in quitting-in relation to the primary outcome of prolonged abstinence and the secondary outcomes of complete abstinence and Week 10 PPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged abstinence was used as the primary outcome (Y) in these analyses, with complete abstinence and Week 10 PPA serving as confirmatory outcome measures. All analyses pooled data across the two treatment groups from the original study (OROS-MPH and placebo), as we previously established that there was no effect of OROS-MPH on smoking cessation outcomes in the study sample (Winhusen et al, 2010). Table 2 shows the results of bootstrapped regressions examining the three predictor variables-desire to quit, perceived difficulty quitting, and expected success in quitting-in relation to the primary outcome of prolonged abstinence and the secondary outcomes of complete abstinence and Week 10 PPA.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings of this study were that osmotic-release oral system methylphenidate (OROS-MPH), when provided in combination with nicotine patch and brief counseling, did improve ADHD symptoms but did not enhance smoking cessation outcomes relative to placebo (plus nicotine patch and counseling; Winhusen et al, 2010). For these secondary analyses, we hypothesized that pretreatment desire to quit (i.e., motivation), expected success in quitting (i.e., self-efficacy), and perceived difficulty quitting would predict smoking cessation treatment outcomes and that treatment adherence (i.e., adherence to nicotine patch, session attendance, and adherence to counseling) would mediate this effect.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…40 Randomized clinical trials of stimulants to aid cessation among ADHD smokers have revealed no evidence that either methylphenidate or amphetamine products are more effective than placebo for facilitating smoking abstinence. 41,42 However, in contrast to some laboratory studies, both stimulant and placebotreated individuals in these studies reduced the number of cigarettes smoked daily, 42,43 and 1 open label study revealed that methylphenidate treatment decreased smoking to below the population rate. 44 Longitudinal studies that have examined smoking outcomes in stimulanttreated ADHD youth provide a more robust approach to evaluate the relationship between stimulant treatment and smoking outcomes.…”
mentioning
confidence: 90%
“…[34][35][36][37][38][39][40] Although clinical trials of treatmentseeking smokers with ADHD have shown that neither methylphenidate nor amphetamine increase smoking, 41,42 studies have not examined how stimulant treatment might influence naturalistic smoking among individuals with ADHD who are not trying to quit. Such studies are necessary to resolve this discrepancy between laboratory studies and clinical trials of smoking cessation.…”
Section: Limitationsmentioning
confidence: 99%